Tanah, Kekerabatan dan Ekonomi Israel Kuno - Nepho Gerson Laoly (STT Injili Indonesia Medan, 2020)
Presenting a picture of ancient Israel is necessary to give the text sharp meaning. Especially when digging up the Bible using the historical-grammatical method. The investigation was carried out with literature research related to Israel including the Hebrew Old Testament text (Hebrew Bible), Ancient Near Eastern literature and archaeological evidence at that time such as the gezer calendar. Land becomes ownership that is passed down from generation to generation, no longer looking for new land as nomadic life does. The kinship system is a tool to prevent a family's economy from entering into hereditary poverty. Agricultural life became the main basis of the economy in ancient Israel although trade was also carried out. The planting and harvesting process is carried out according to the specified schedule. This provides a neat economic picture for an ancient nation. With the three elements running well, ancient Israel would become a strong and established nation in the midst of other nations. Living life as God gave it really made ancient Israel strong. This article describes Israel before the exile, a picture we can see before the moral decline that plagued other aspects of ancient Israel's life as well.Keywords: Israel ; Land; Kinship; Economy; Gezer